Women in the Cuban Political Power Structures: Figures and Normative Context (1974-2021) - Guzman Hernández, Teodoro Yan (2021)
The representation of women in the power structures in Cuba is a sign of their empowerment after the Revolution triumph, but are there mechanisms to favor the presence of women in some structures of the political system in Cuban? Does woman have similar representation and potential influence in the supreme organ of State than in the superior leading force of the State and society? The purpose of this paper is to analyze those particularities of the political system and electoral law in Cuba that have conditioned female representation, as well as their real political influence in certain state organs and in the structures of the Communist Party, from the 1970s to date. For this purpose, a historical-logical analysis of the political empowerment of women is carried out and through statistical analysis, the position of women in different power structures is compared, based on the interpretation of those legal norms that illustrate the political relevance of certain organs and structures of the State and of the party, respectively.